2021
DOI: 10.1038/s41420-021-00592-z
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes promote hepatocellular carcinoma by activating the ERK signaling pathway and miR-942-3p/MMP9 axis

Abstract: In China, hepatocellular carcinoma (HCC) is considered a malignant tumor with poor prognosis, frequent metastasis, and a high relapse rate. Telocytes (TCs) participate in tumorigenic, invasive, and migratory processes by secreting functional proteins and transmitting cell-to-cell information, but their functions in HCC are still unknown. TC counts and MMP9 expression in liver cancer tissues were measured using immunohistochemistry, western blotting, and RT-PCR. Primary TCs from liver para-cancer tissues were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In our previous study, we elucidated that TCs promoted the metastasis of HCC by secreting MMP9, which is classified as the gelatinase subtype of the MMP family. We also found that multiple growth factors from cancer cells contributed to activating the MAPK signaling pathway, resulting in MMP9 overexpression (Kochi et al, 2020; Xu et al, 2021). Notwithstanding, small molecules take part in the process of oncogenesis, and somatic mutations as a pathogenic element for the onset of malignancy and should not be ignored.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous study, we elucidated that TCs promoted the metastasis of HCC by secreting MMP9, which is classified as the gelatinase subtype of the MMP family. We also found that multiple growth factors from cancer cells contributed to activating the MAPK signaling pathway, resulting in MMP9 overexpression (Kochi et al, 2020; Xu et al, 2021). Notwithstanding, small molecules take part in the process of oncogenesis, and somatic mutations as a pathogenic element for the onset of malignancy and should not be ignored.…”
Section: Discussionmentioning
confidence: 92%
“…Focusing on tumorigenesis, TCs were reported as an accelerative factor to promote the invasion and migration of cancer and cell proliferation (Klein et al, 2020). For instance, we demonstrated that when PDGF‐α stimulated TCs, the Raf/MEK/ERK signaling pathway was activated to increase MMP9 expression, which was a molecular mechanism by which TCs promote HCC metastasis (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, as telocytes release microvesicles, they are thought to be involved in contactless intercellular cross-talk [ 51 ]. In hepatocellular carcinoma, telocytes were found to promote metastasis by the production and secretion of matrix metalloproteinase 9 [ 52 ].…”
Section: Pancreas—basic Relationshipsmentioning
confidence: 99%
“…The protocol of TCs identi cation in the liver tissue could be referenced in our previous study(Suppl Fig 1-A) [14] .…”
Section: Telocytes Identi Cationmentioning
confidence: 99%
“…Currently, the function of TCs in the development of cancers received more and more attention. In our previous study, we found that low expressions of miR-942-3p in TCs promoted matrix metalloproteinase-9(MMP9) secretion to accelerate the metastasis of HCC [14] , but the molecular mechanism was still unknown. Whether HCC cells-derived exosomes possess the contribution to impact TCs needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%